2018
DOI: 10.1016/j.vetimm.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasomes in livestock and wildlife: Insights into the intersection of pathogens and natural host species

Abstract: The inflammasome serves as a mechanism by which the body senses damage or danger. These multiprotein complexes form in the cytosol of myeloid, epithelial and potentially other cell types to drive caspase-1 cleavage and the secretion of the pro-inflammatory cytokines IL-1β and IL-18. Different types of inflammasomes, centered on (and named after) their cytosolic NLRs, respond to signals from bacteria, fungi, and viruses, as well as "sterile inflammatory" triggers. Despite the large body of research accumulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 102 publications
(103 reference statements)
1
10
0
Order By: Relevance
“…The gene MAP2K7 is involved in the signal transduction mediating the cell responses to environmental stresses and is a candidate region for milk yield in buffalo (Du et al, 2019); LRRC8E forms volume-regulated anion channels, a key structure that regulates osmotic volume regulation (König and Stauber, 2019); and OXCT1 plays a role in ketone body catabolism in mammary glands during lactation, and it is related to fat percentage (Bionaz and Loor, 2008). The QTL regions associated with milk protein in this study have been previously found to be related to SCS (SNAPC2, CTXN1, ELAVL1, CCL25, FBN3, CERS4, CD320, NDUFA7, KANK3, ANGPTL4, RAB11B, MYO1F, ADAMTS10, ACTL9, GFUS, PYCR3, TIGD5, EEF1D, NAPRT, MROH6, GSDMD, ZC3H3, MAFA, and RHPN1) and immune system (TRIP10, C3, TNFSF14, CD70, and TNFSF9; Griesbeck-Zilch et al, 2009;Li et al, 2010b;Chen et al, 2015;Vrentas et al, 2018;Wu et al, 2019;Rabe et al, 2020). In addition, MicroRNA MIR339B plays a regulatory role in hematopoiesis, mastitis, and breast cancer (Bruchova et al, 2007;Wu et al, 2010;Li et al, 2014).…”
Section: Candidate Genes For Ppsupporting
confidence: 57%
“…The gene MAP2K7 is involved in the signal transduction mediating the cell responses to environmental stresses and is a candidate region for milk yield in buffalo (Du et al, 2019); LRRC8E forms volume-regulated anion channels, a key structure that regulates osmotic volume regulation (König and Stauber, 2019); and OXCT1 plays a role in ketone body catabolism in mammary glands during lactation, and it is related to fat percentage (Bionaz and Loor, 2008). The QTL regions associated with milk protein in this study have been previously found to be related to SCS (SNAPC2, CTXN1, ELAVL1, CCL25, FBN3, CERS4, CD320, NDUFA7, KANK3, ANGPTL4, RAB11B, MYO1F, ADAMTS10, ACTL9, GFUS, PYCR3, TIGD5, EEF1D, NAPRT, MROH6, GSDMD, ZC3H3, MAFA, and RHPN1) and immune system (TRIP10, C3, TNFSF14, CD70, and TNFSF9; Griesbeck-Zilch et al, 2009;Li et al, 2010b;Chen et al, 2015;Vrentas et al, 2018;Wu et al, 2019;Rabe et al, 2020). In addition, MicroRNA MIR339B plays a regulatory role in hematopoiesis, mastitis, and breast cancer (Bruchova et al, 2007;Wu et al, 2010;Li et al, 2014).…”
Section: Candidate Genes For Ppsupporting
confidence: 57%
“…While current knowledge of the role of the inflammasome in livestock vectors of disease is still limited, there is an expanding literature on the impact of the NLRP3 inflammasome in multiple livestock species, especially swine (reviewed in Vrentas et al). 22 Expansion of our characterization of inflammasomes in bovine species has the potential to contribute to our understanding of differences between either bovine and human, or bovine and wildlife, species in terms of susceptibility to zoonotic infections, differences in disease virulence and persistence, and/or differences in vaccine responses.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the detailed characterization of inflammasome pathways in rodent and human systems, our understanding of inflammasome activation in livestock hosts of disease is limited (reviewed in Vrentas et al). 22 Recently, the first characterization of NLRP3 activation in bovine cells was published, 23 but nothing is known of NLRP1 responses in these species, despite the fact that herbivores like cattle and bison, rather than rodents, are the most common hosts for anthrax in natural environments. Similarly, shedding of Shigella and Listeria from large ruminants is an important contributor to the environmental spread of these bacteria, which can also cause active disease in ruminants.…”
Section: Introductionmentioning
confidence: 99%
“…202 However, given its inextricable role in infectious diseases, pyroptosis has been also recently implicated in numerous diseases of domestic animals, such as porcine reproductive and respiratory syndrome virus (PRRSV) infection and classical swine fever virus infection, in which it causes release of IL-1beta by macrophages. 305 The finding of increased NLRP3 labeling in the glomeruli of dogs infected with Leishmania infantum led to the hypothesis regarding a potential role of the NLRP3 inflammasome engagement in the pathogenesis. 83 Although little is known about inflammasome responses in cattle, in vitro studies demonstrated caspase-1 activation in bovine herpesvirus 1 infections, as well as IL-1beta secretion from bovine monocyte-derived macrophages in the presence of bovine viral diarrhea virus type 2 and LPS.…”
Section: Pyroptosismentioning
confidence: 99%